Comparative effects of Piprazine of citrate® and papaya seeds on Ascaridia galli in layers Harco - Dougnon TJ,; Tobada P,; Assogba MN,; Kpodékon TM, (International Journal of Phytomedicine, 2012)
The present study has been realised in the farm ‘protein for all’ (PPT) located in Tori Sogbe in the Atlantique-Littoral province, from May to June 2011. A number of 300 layers Harco have been used for the test. They haven’t been detected before the experience which was to test the anti-parasitical efficiency of citrate of pipérazine® and of papaya seeds on Ascaridia galli. The weights of the eggs have been taken into a count before and after the treatment of the layers. The 300 hens have been separated into 6 groups of 50 hens which have been differently treated: The group 0, group of witness receives no treatment. Treatment 1 (2.5g/L of citrate of pipérazine® solution) for the group 1; treatment 2 (2.5g/L of papaya seeds solution) for the group 2 ; treatment 3 (2g/L of papaya seeds solution) for group 3 ; treatment 4 (3g/L of papaya seeds solution) for group 4 ; treatment 5 (4g/L of papaya seeds solution) for group 5. At state 1, it is to say before the treatment, the average quantity of the Eggs Per Gram (EPG) are statistically the same. In other words, the situation before the treatment is identical with the 6 groups. After the treatment, it is to say at state 2, we have noticed a difference highly significative between the treatments with an efficiency rate of -50% for the witness group ; 80% for the treatment 1 ; -14% for the treatment 2 ; 4% for the treatment 3 ; 16% for the treatment 4 and 65% for the treatment 5. In conclusion, we can retain that papaya seeds, no matter what is their dosage, have reduced significantly the number of EPG comparing to the witness group. But that reduction remains lower than the one of citrate of pipérazine® (2.5g/L of the solution). More over, the more the dosage of papaya seed increases, the more the reduction of Ascaridia galli parasitical eggs is important.